(untitled) - Mackie, Gerry (Cambridge,New York, 2003)
This volume is a revision and expansion of author’s Ph.D thesis, "Is democracy impossible? a preface to deliberative democracy," University of Chicago, 2000.
Keywords: Democracy,Chế độ dân chủ